Pneumococcal Encounter With the Blood–Brain Barrier Endothelium - Anil, Anjali; Banerjee, Anirban (Frontiers in Cellular and Infection Microbiology, 2020)
Meningitis, the inflammation of the protective membrane surrounding the brain and spinal cord (known as meninges), is a condition associated with high mortality rates and permanent neurological sequelae in a significant proportion of survivors. The opportunistic pathogen Streptococcus pneumoniae (SPN/pneumococcus) is the leading cause of bacterial meningitis in adults and older children. Following infection of the lower respiratory tract and subsequent bloodstream invasion, SPN breaches the blood–brain barrier endothelium for invasion of the central nervous system. Transcytosis, a mode of passage through the endothelial cells has been identified as the predominant route of pneumococcal blood–brain barrier trafficking. Herein, we review the interactions enabling SPN invasion into the brain endothelial cells, events involved in the tug-of-war between pneumococcal virulence factors and host intracellular defense machineries and pneumococcal strategies for evasion of host defenses and successful transendothelial trafficking.